SILAC‐based quantitative proteomic analysis of secretome between activated and reverted hepatic stellate cells. Issue 17 (4th August 2014) - Zhang, Hongyu; Wu, Peng; Chen, Fangyan; Hao, Yunwei; Lao, Yuanxiang; Ren, Liangliang; Sun, Longqin; Sun, Wei; Wei, Handong; Chan, Daniel W.; Jiang, Ying; He, Fuchu; et al.
<x xml:space="preserve">Abstract</x> Activated hepatic stellate cell (HSC) is the main myofibroblast cell in the liver fibrosis (LF). An important characteristic of the recovery of LF is not only the apoptosis of activated HSCs but also reversal of myofibroblast‐like phenotype to a quiescent‐like phenotype. Understanding the changes of secreted proteins in the reversion of activated HSCs may provide the broader view of cellular regulatory networks and discover candidate markers or targets for therapeutic strategies of LF. In this study, stable isotope labeling with amino acids (SILAC) combined with linear ion trap‐Fourier transform ion cyclotron resonance mass spectrometer (LTQ‐FT MS) was performed on in vitro activated HSCs and reverted HSCs to obtain a proteomic view of secretory proteins. In total, 330 proteins showed significant differences in reverted HSCs. Among these, 109 upregulated proteins were mainly involved in amino acid metabolism pathway and glucose metabolism pathway using GeneGO/MetaCore software, while 221 downregulated proteins are closely associated with HSCs activation, such as cytoskeleton remodeling, chemokines, and cell adhesion. Additionally, a set of novel proteins associated with HSCs activation and reversion were validated by Western blotting in the cell secretion and in the sera of LF, including vitronectin, laminin beta 1, and ubiquitin conjugation factor E4B. Our study provided the valuable insight into the mechanisms in the reversion of activated HSCs and identified some potential biomarkers of LF in clinical studies. All MS data have been deposited in the ProteomeXchange with identifier PXD000773 (http://proteomecentral.proteomexchange.org/dataset/PXD000773).